Case Report: Significant Response to Immune Checkpoint Inhibitor Camrelizumab in a Heavily Pretreated Advanced ER+/HER2− Breast Cancer Patient With High Tumor Mutational Burden - Wang, Rong; Yang, Yuchen; Ye, Wei-Wu; Xiang, Jianxing; Chen, Songan; Zou, Wei-Bin; Wang, Xiao-Jia; Chen, Tianhui; Cao, Wen-Ming (Frontiers in Oncology, 2021)
Endocrine treatment as well as CDK4/6 inhibitors have become standard of care for estrogen receptor positive (ER+) breast cancer. Although immune checkpoint inhibitors (ICIs) have shown promising antitumor activity in a variety of cancer types, only limited success has been achieved for metastatic breast cancer (mBC) patients, especially the ER+ subtype, which usually exhibit lower tumor mutation burden (TMB) compared with other subtypes and therefore perceived as immunologically quiescent. Here we present a case of an ER+/HER2- but TMB-high mBC patient who had significant response to combination therapy with anti-PD-1 antibody camrelizumab and vinorelbine and obtained partial response (PR) with a progression-free survival (PFS) of 5 months after failure of multiple lines of therapy. Our case indicates that TMB may serve as a potential biomarker in immunotherapy selection for normally immunologically “cold” tumors such as ER+ mBC, also molecular monitoring during the whole treatment course plays an important role in patient management.